The effect of an ultra-endurance running race on mucosal and humoral immune function - Pacque, P. F.; Booth, C. K.; Ball, M. J.; Dwyer, D. B. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: There are reports of the effect of endurance exercise on mucosal immune function and of the effect of short duration exercise on humoral immune function. However, little is known of the effect of endurance exercise on humoral immune function and the related risk of infection. This study examined the effects of an ultra-endurance running race on salivary immunoglobulin-A (s-IgA), serum IgA, leukocyte subset concentrations and the incidence of upper respiratory tract infections (URTI). Methods: Thirteen male and 4 female competitors provided saliva samples and blood before and at several times after the running race. Self-reported symptoms of URTI were also recorded for 2 weeks before and 2 weeks after the race. Results: Salivary IgA secretion rate (P=0.005) and ratio to osmolality (P=0.006) were lower immediately postrace and decreased further for at least 2 more h. s-IgA secretion rate had not returned to normal the next morning (P=0.009). Serum IgA concentration was lower post- than prerace (P=0.003) and was even lower the next morning (P<0.001). Leukocyte concentration was elevated postrace (P<0.001), mainly because of an increase in neutrophils (P<0.001) and both remained high the morning after the race (P<0.001). Lymphocyte concentration decreased postrace (P<0.001) and was still depressed the next morning (P=0.032). The incidence of symptoms of URTI was the same in the two 2-week periods before and after the race. Conclusion: These findings support the hypotheses that an ultra-endurance run may adversely affect mucosal immunity and cause significant changes in the concentration of leukocyte subsets.